Optimization of slightly acidic electrolyzed water spray for airborne culturable bacteria reduction in animal housing - Weichao, Zheng; Li, Ni; Xue, Hui; Baoming, Li; Jiafa, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Slightly acidic electrolyzed water (SAEW) spray has been considered as a novel approach for airborne bacteria reduction in animal housing. This study aimed to optimize the operating parameters of SAEW spray based on the size distribution of sprayed aerosols, the available chlorine travelling loss in sprayed aerosols, and the reduction efficiency of airborne culturable bacteria (CB). The optimized operating parameters were the nozzle orifice diameter and the spray pressure. The size distribution characteristics of sprayed SAEW aerosols under different operating parameters were quantified. The pH and available chlorine concentrations of the original SAEW solution and the SAEW aerosols collected at 0 m, 0.25 m, 0.50 m, 0.75 m, and 1.00 m from the spray nozzle head were analyzed. A bioaerosol nebulizing generator was used to simulate animal housing environment in an environmentally-controlled chamber. Six SAEW spray trials under different operating parameters were conducted at a spray dosage of 80 mL/m2 in the chamber. Airborne CB concentrations before and after spray were measured to investigate the reduction efficiency of airborne CB. Dv(50), the volume-based diameter below which 50% of the particle being present, increased with the nozzle orifice diameter and decreased with the spray pressure. The travelling loss of available chlorine in the sprayed SAEW aerosols was greatly dependent on Dv(50). SAEW spray with medium size sprayed aerosols (Dv(50) = 86.62 μm, 67.94 μm, and 54.53 μm) showed significantly higher airborne CB reduction efficiencies than large (Dv(50)=121.80 μm and 96.00 μm) or small size aerosols (Dv(50) = 42.57 μm). The spray operating parameters that provide medium size sprayed aerosols (Dv(50) ~ 60-90 μm) are recommended for SAEW spray in animal housing.Keywords: animal housing, bioaerosol, available chlorine, size distribution, air quality, poultry and livestockDOI: 10.3965/j.ijabe.20160904.2366Citation: Zheng W C, Ni L, Hui X, Li B M, Zhang J F. Optimization of slightly acidic electrolyzed water spray for airborne culturable bacteria reduction in animal housing. Int J Agric & Biol Eng, 2016; 9(4): 185－191.